CrossCheck. - Lifset, Reid (Journal of Industrial Ecology, 2011)
The writer suggests that the world of scholarly publishing continues to evolve at a rapid pace. The writer notes that those industrial ecologists active in teaching know that Web-based tools for the detection of student plagiarism are widely available. The writer focuses on the fact that knowledge is abundantly available and that the biggest complication is to rescue one's own text.